Porous organic frameworks for preferable adsorption of trans-1, 2-diols over cis-1, 2-diols. (August 2022) - Zensen, Tobias; Röper, Theresa; Fuchs, Thomas; Sackers, Nina M.; Bachmann, Stephanie; Pöppler, Ann-Christin; Jupke, Andreas; Palkovits, Regina; Delidovich, Irina
Highlights: Porous organic frameworks for adsorption of vic- diols. Preferable adsorption of trans-vic -diols over cis-vic -diols is possible. Adsorption mechanism and selectivity depend on material structure. MAS NMR to explore adsorption mechanisms. Material application in a dynamic column setup. Novel separation processes are of utmost importance for a sustainable development of the chemical industry. In this work we show that polymer organic frameworks (POF) synthesized via condensation of melamine and a dialdehyde spacer exhibit superior selectivity towards adsorption of trans-vic -diols over cis - vic -diols. Mixtures of trans - and cis -1, 2-cyclohexanediol as well as meso ‑ and ( R, R )-2, 3-butanediol were applied for separation. Binding takes place due to cooperative hydrogen bonding of OH-groups of trans-diols to a nitrogen atom of the melamine ring and an NH-fragment of the aminal motif. The formation of the hydrogen bonds upon adsorption was supported by solid-state NMR experiments of samples after adsorption. Utilization of an aprotic solvent with low relative permittivity is of importance to achieve high adsorption capacities. The length of the dialdehyde spacer presents the major parameter governing the size of the micropores and thus the selectivity towards the trans -isomer. The best results were obtained for a POF prepared using 4, 4′-biphenyldicarbaldehyde as spacer and bearing micropores with an average diameter of 0.67 nm. The average pore aperture is thus larger than the size of the tested diols, which are ca. 0.6 nm in length. Utilizing of isophtalaldehyde and phthalaldehyde as spacers gave rise to the sorption materials with average pore diameters of ca . 0.6 nm, comparable to the sizes of diol molecules. Adsorption of cis - and trans -diols onto the latter materials occurred owing to trapping in the pores, which resulted in strong van der Waals interactions leading to similar adsorption affinities of cis - and trans - isomers. The results of adsorption under batch and continuous conditions evidence the high potential of POF with 4, 4′-biphenyldicarbaldehyde as spacer for adsorptive separation of trans - and cis -diols. Graphical abstract: Image, graphical abstract